SETTLEMENT MODEL OF DYNAMICS OF NONLINEAR SYSTEMS - M. R. Guseynova; R. V. Guseynov (Вестник Дагестанского государственного технического университета: Технические науки)
Developed computational model of the dynamics of the cutting process, taking into account the characteristics of the nonlinearity strength. The method of construction of the approximating curve.